Peanut Ball Sebagai Intervensi Nonfarmakologis Terhadap Intensitas Nyeri Persalinan Kala I: Literature Review - Dian Pratiwi (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2026)
Background: First-stage labor pain is a physiological process experienced by nearly all women during childbirth and may affect maternal comfort, childbirth experience, and labor progress. Various non-pharmacological interventions have been developed to reduce labor pain, one of which is the use of a peanut ball. Objective: This literature review aimed to analyze the effectiveness of the peanut ball as a non-pharmacological intervention for reducing first-stage labor pain intensity. Methods: A systematic literature review was conducted following the PRISMA 2020 guidelines. Articles published between 2022 and 2026 were identified through PubMed, ScienceDirect, Wiley Online Library, SpringerLink, ProQuest, and Google Scholar. Article selection was performed using predefined inclusion and exclusion criteria based on the PICOS framework, resulting in eight eligible studies for analysis. Results: The synthesis demonstrated that the use of a peanut ball was generally effective in reducing first-stage labor pain intensity, improving maternal comfort and satisfaction, and promoting a more positive childbirth experience. Several studies also reported a tendency toward shorter labor duration, although the findings remained inconsistent. The effectiveness of the peanut ball is associated with its ability to facilitate maternal position changes, enhance pelvic mobility, and optimize fetal head descent during labor. Conclusion: The peanut ball is a safe, practical, and effective non-pharmacological intervention for reducing first-stage labor pain and has the potential to be integrated into evidence-based maternity care practices.